RE-TRABECULECTOMY + 5-FLUOROURACIL IN PRIMARY ANGLE CLOSURE GLAUCOMA PATIENTS AGGRAVATED BY CONSUMPTION OF SCHIZOAFFECTIVE DRUG: Poster Presentation - Case Report - Resident - Fidalia; Syafridon, M Fadhil; Sari, Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : PACG occurs when the anterior chamber angle is occluded by the iris thus reducing aqueous humor outflow. Most schizoaffective patients use anticholinergic drugs which may result in iridocorneal angle closure through deposition. This article reported a Re-Trabeculectomy + 5 FU surgery in PACG which was aggravated by the use of schizoaffective drugs Case Illustration : A 43 year old woman, underwent Re-Trabeculectomy + 5 FU on LE after increasing IOP and regularly took schizoaffective drugs. Tapering of schizoaffective therapy was done 1 month preoperatively. Patient presented with LE UCVA of 3/60 and LE IOP is 30.9 mmHg with three anti- glaucoma medications. LE examinations revealed VH1 AC, bayonet sign and cupping on funduscope, closed angle on gonioscope, nasal step defect on humphrey and diffuse RNFL thinning on OCT. On the first postoperative day LE IOP is 18.5 mmHg. The schizoaffective therapy was re-initiated from psychiatric and evaluation was done weekly Discussion : Re-trabeculectomy surgery have been done considering the failure of the first trabeculectomy and administration of 5-Fluorouracil as an anti-fibrosis. The benefits of reducing preoperative dose of schizoaffective drugs for a month due to having an anticholinergic effect and reduces IOP by 5 mmHg. Psychiatrists and ophthalmologists work together to try to administer basic schizoaffective drug doses and evaluate IOP to keep it under control. Conclusion : The re-operative action was carried out by adding anti-fibrosis and cooperating with psychiatry for postoperative tapering of schizoaffective drugs. Long-term use of antidepressant drugs and benzodiazepines increases PACG.